Virtual Therapy Complementary Prehabilitation of Women Diagnosed with Breast Cancer—A Pilot Study - Czech, Oliver; Siewierska, Katarzyna; Krzywińska, Aleksandra; Skórniak, Jakub; Maciejczyk, Adam; Matkowski, Rafał; Szczepańska-Gieracha, Joanna; Malicka, Iwona (International journal of environmental research and public health, 2022)
Breast cancer is becoming an important issue due to its various consequences and epidemiology. Studies are showing that it extremely impacts the mental health as well as the physical activity of the patients. In addition to the most common symptom, which is fatigue, patients also have problems with the quality of sleep. Therefore, this study aimed to evaluate the effectiveness of virtual reality (VR) therapy in improving the mental state and quality of sleep, as well as increasing the physical activity (PA) of patients diagnosed with breast cancer. The study was conducted in a hospital’s Breast Unit and included patients at the time of diagnosis of malignant breast cancer. A total of 16 subjects randomly divided into experimental (n = 9), and control (n = 7) groups were measured with the Beck Depression Scale, Mental Adjustment to Cancer Scale, International Physical Activity Questionnaire, and Pittsburgh Sleep Quality Index at two timepoints. The experimental intervention consisted of a 2-week (8 sessions) Virtual Therapeutic Garden (VRTierOne) procedure performed daily for about 15 min. Significant differences were identified between groups in the interactions between the main factors seen in the destructive style of the Mini-Mac scale: F(1.14) = 4.82, p = 0.04, and between multiple experiments: F(1.14)= 5.54, p = 0.03 showing a significant reduction in the destructive style of coping with the disease in the study group after therapy (32.44 vs. 28.33, p = 0.003). The level of main effects [study] for the constructive style is F(1.14) = 3.93, p = 0.06 with a significant increase in constructive style in the study group (43.33 vs. 45.33, p = 0.044). Significant differences in levels of depression between multiple experiments: F(1.14) = 5.04, p = 0.04, show a significant reduction in the severity of depressive symptoms was found in the experimental group after therapy (13.33 vs. 8.11, p = 0.02). However, the analysis did not show significant differences between group analyses (p = 0.25). It seems that VR reduces the severity of depressive symptoms and reduces the destructive style and can be an effective option in improving the mental state of patients diagnosed with breast cancer.